Reviews and Responses for Improving Efficiency Through the Publication of Expected Distances for Standard Terminal Arrival Routes - Krummen, Jan; Krauth, Timothé; Allendorf, Jan; Monstein, Raphael; Polishchuk, Tatiana; Sun, Junzi (Journal of Open Aviation Science, 2025)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2024.7894